HASIL BELAJAR KOGNITIF IPA FISIKA MELALUI PENERAPAN PENDEKATAN OPEN-ENDED POBLEM PADA MATERI CAHAYA DI SMPN 17 PEKANBARU - Hasmiana '; Mitri Irianti; Azhar ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research aimed to describe students learning result by applying approach open-ended problem. Type of this research is a pre-experimental, with intact-group comparison design. The population and sample of this research is students class VIII at SMPN 17 Pekanbaru, total of 240 students. Sample of this using two class with technik random sampling, experimental class and control class. The data in this research is a score of absorption and efectivity learning physics by implementation of approach open-ended problem and analysis of the data uses descriptive analysis. The result of this research, score absorption and efectivity of students there is a difference, score average absorption and efectivity is 74,5 % at experimental class and then 62 % at control class. Therefore, it can be concluded that the implementation approach open-ended problem able to improve the learning result of student at SMPN 17 PekanbaruKey Words: Approach Open-ended Problem , Cognitive Learning Result